Women and WorkChoices : impacts on the low pay sector - Elton, Jude.; University of South Australia. Centre for Work and Life. (Adelaide : Centre for Work + Life, Hawke Research Institute for Sustainable Societies, 2007)
Provides a comprehensive picture of the nature and extent of these changes for individuals requires close study not just of pay packets, but of total earnings, hours worked, employment security, employee voice, and workplace climate. Such a study can be conducted by means of large, comprehensive surveys and / or by qualitative analysis of experience (for example, by means of in-depth interviews), and preferably by a combination of the two methodologies.
"August 2007".
Includes bibliographical references.
Keywords: Australia; Women -- Employment -- Australia; Women -- Australia -- Economic conditions; Industrial laws and legislation -- Social aspects -- Australia; Labor laws and legislation -- Social aspects -- Australia